Classroom interaction patterns of high and low achievers at an undergraduate private university in Dubai - Salameh, walid; A. Sathakathulla, A. (SPC Journal of Education, 2019)
This research emphasizes a study which was conducted to observe the patterns of classroom interactions of both high and low achieving students at a private university in Dubai. The main aspects of the research were: (1) Frequency of interactions; (2) Nature of interactions; and (3) Reasons for avoided interactions initiation. It was determined that more interactions were initiated by high achieving students than by low achieving students, although low achieving students attained a similar level of interaction as high achievers when discussion was initiated by the teacher. It was also observed that low achieving students prefer privacy when asking a question or checking for correctness of answers, whereas high achievers exhibited more confidence towards asking questions and providing comments on discussion. Surveying students regarding the reasons they avoid initiating interactions revealed that high achieving students lack motivation as they are probably under-challenged, while low achieving students lack confidence as well as motivation. Â Â Â